The growth of process safety practice in China. Issue 1 (16th January 2023) - Meng, Yifei; Hu, Yeyao; Li, Weidong; Liu, Yi; Zhao, Dongfeng; Willey, Ronald J.
Abstract: Implementation of modern process safety practices came to China around the turn of the millennium. Compared to other developed countries. It is a relatively late start. However, within a period of 20 short years, remarkable results have been achieved under the joint efforts of many parties. Firstly, this paper introduces four major contributors that influence the development of process safety in China. These are the Chinese government, industry associations and consulting companies, production enterprises, and research institutes and universities. Among them, the government guides the development of process safety in China through policy guidance and the establishment of government projects. It also provides the driving force for research. Secondly, this paper reviews the main process for the development of process safety in China. It divides the development of process safety in China into three stages: namely sporadic contact, active cooperation, and comprehensive development, according to the frequency and leading party of process safety practice activities. Finally, a systematic review of China's process safety practices is conducted from four aspects: international communication and cooperation, process safety technology promotion, safety management system promotion, and personnel training promotion.